KEPEMIMPINAN TRANSFORMASIONAL KEPALA DESA DALAM PEMBANGUNAN INFRASTRUKTUR JALAN DI DESA BESUKI - Andreas Saputra; Bella Saka Aulya; Febriana Sal Sabila; Anang Sugeng Cahyono (Gapenas Publisher, 2023)
This article examines the transformational leadership of the village head in the construction of road infrastructure in Besuki Village, Tulungagung District. The purpose of this research is to describe the role of village heads in road construction issues using a transformational leadership style. The research methodology used in this article is descriptive-qualitative. The research instruments are observation and literature study using books, scientific papers, journals, and others. The data source for this article is the result of observation as primary data and literature as secondary data. The results of the research using transformational leadership indicators (Robbin) consist of: 1) Charisma has been running effectively. This is known from the delivery of its vision and mission to the community contained in the infrastructure development plan. 2) Inspirational Motivation: This can be seen from the village head's giving motivation to his employees regarding infrastructure development. 3) Intellectual stimulation is carried out well by giving subordinates the freedom to convey their ideas and opinions regarding the problems that occur. 4) Individual attention Providing training related to existing problems, especially related to infrastructure development, to develop the skills of his subordinates The application of transformational leadership from the Head of Besuki Village has a major influence on solving problems, especially road construction and road infrastructure development in Besuki Village